Efficacy of Radiotherapy in Patients with Relapsing Primary Rosai–Dorfman Disease of the Nasal Cavity - Caius-Codrut Sarafoleanu; Florentina-Carmen Badea; Alina-Maria Georgescu; Gabriela-Cornelia Musat; Anica Andrei; Ionut Tanase (Medicina)
Rosai–Dorfman disease (RDD) is a rare proliferative disorder characterized by an overproduction of a type of immune cell called histiocytes, with unknown etiology. Although extranodal involvement is not uncommon, it is rarely seen within the nose. The available data are limited, and currently, there are no established guidelines for managing RDD. Different therapeutic options have been described, including corticosteroids, surgery, radiotherapy, or chemotherapy. This study aims to evaluate the potential benefit of radiotherapy in patients with nasal Rosai–Dorfman disease to improve the current diagnostic and therapeutic management. Herein, we report the case of a 54-year-old female patient with nasal RDD refractory to systemic corticosteroid therapy and transnasal endoscopic resection. She received fractionated low-dose radiotherapy with a total dose of 30 cGy administered in 2 cGy daily fractions. Complete remission was achieved, highlighting the potential role of radiotherapy as an effective therapeutic option for relapsing or steroid-refractory cases. This is one of the few well-documented cases reported with nasal Rosai–Dorfman disease treated with radiotherapy. Ongoing research on novel therapies offers hope for improved outcomes in relapsing cases that fail to respond to conventional treatments.